2007
DOI: 10.1258/002367707780378140
|View full text |Cite
|
Sign up to set email alerts
|

Nociception after intraperitoneal injection of a sodium pentobarbitone formulation with and without lidocaine in rats quantified by expression of neuronal c-fos in the spinal cord – a preliminary study

Abstract: SummaryAfter a search on Medline, it appears that intraperitoneal injection of sodium pentobarbitone is often used for anaesthesia and euthanasia of rodents. In the present pilot study in rats, spinal nociception after intraperitoneal injection of sodium pentobarbitone, with and without lidocaine, was examined by estimation of the number of c-fos-expressing neurones in the spinal dorsal horn. One group of rats received an intraperitoneal injection of 0.4 mL/kg sodium pentobarbitone (100 mg/mL; n ¼ 4). Another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 20 publications
(21 reference statements)
2
30
1
Order By: Relevance
“…We used inhaled isoflurane to avoid any direct irritation within the peritoneum from the anaesthetic whereas Hazebroek et al used intraperitoneal pentobarbitone administered every 30 min. Pentobarbitone is known to have irritant effects [35] which may have significantly contributed to the mesothelial damage. This hypothesis is supported by the fact that the group with mechanical abdominal wall lifting in the study showed similar damage to the three insufflation groups, indicating that pneumoperitoneum was not the cause of the mesothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…We used inhaled isoflurane to avoid any direct irritation within the peritoneum from the anaesthetic whereas Hazebroek et al used intraperitoneal pentobarbitone administered every 30 min. Pentobarbitone is known to have irritant effects [35] which may have significantly contributed to the mesothelial damage. This hypothesis is supported by the fact that the group with mechanical abdominal wall lifting in the study showed similar damage to the three insufflation groups, indicating that pneumoperitoneum was not the cause of the mesothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed repeated dosing with lower volume of pentobarbitone to be safer at maintaining anesthesia, because the margin between anesthetic and lethal doses for pentobarbitone is very narrow . However, concerns are raised because of the low pH of the pentobarbitone solution . Due to pain that may be caused by the low pH, use of pentobarbitone as an anesthetic is generally discouraged unless it was for nonrecovery procedures.…”
Section: Resultsmentioning
confidence: 99%
“…34 However, concerns are raised because of the low pH of the pentobarbitone solution. 35 Due to pain that may be caused by the low pH, use of pentobarbitone as an anesthetic is generally discouraged unless it was for nonrecovery procedures. Similarly, the use isoflurane as an anesthetic for glucose tolerance test is discounted since it offsets the glycemic profile.…”
Section: Resultsmentioning
confidence: 99%
“…Current guidelines do not indicate a specific dose of sodium pentobarbital for euthanasia, although 200 mg/kg or 3 times the anesthetic dose have been suggested [5]. There are several potential drawbacks associated with IP PB injection, including misinjection, variability in effect and pain [7,[16][17][18][19][20][21][22]. An important factor contributing to variability of drug effect (speed of onset and success) is misinjection, with deposition of injectate into intra-abdominal fat, abdominal viscera or the subcutaneous space.…”
Section: Sintroductionmentioning
confidence: 99%
“…Specifically, exhibition of writhing (defined as the contraction of the abdomen and extension of the hind legs), grossly visible inflammation of abdominal viscera at necropsy and a measurable increase in spinal cord cFos have been reported following IP injection of pentobarbital [16,17,21,22].…”
Section: Sintroductionmentioning
confidence: 99%